Logarithmic coefficient of the entanglement entropy of a Maxwell field - Casini, Horacio German (2020)
We elucidate the mismatch between the A-anomaly coefficient and the coefficient of the logarithmic term in the entanglement entropy of a Maxwell field. In contrast to the usual assumptions about the protection of renormalization group charges at the infrared, the logarithmic term is different for a free Maxwell field and a Maxwell field interacting with heavy charges. This is possible because of the presence of superselection sectors in the IR theory. However, the correction due to the coupling with charged vacuum fluctuations, that restores the anomaly coefficient, is independent of the precise UV dynamics. The problem is invariant under electromagnetic duality, and the solution requires both the existence of electric charges and magnetic monopoles. We use a real-time operator approach, but we also show how the results for the free and interacting fields are translated into an effective correction to the four-sphere partition function.